ANALISIS IMPLEMENTASI KEBIJAKAN STRATEGI PENGELOLAAN INFRASTRUKTUR YANG EFEKTIF, TRANSPARAN DAN PARTISIPATIF (STRATEGI PASTI PAS) DI KOTA PAYAKUMBUH - Nurlatifa, Adinda; Yusran, Rahmadani (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This research aims to analyze the variables influencing the implementation of the Policy Strategi Pengelolaan Infrastruktur yang Efektif, Transparan dan Partisipatif (Strategi PASTI PAS) in the Payakumbuh city. This policy is motivated by several critical problems, including the low level of legalization of state land ownership, low community participation in infrastructure management, and the limitations of the public information and communication system. Referring to the implementation model of Van Meter and Van Horn (1975), this study examines six variables that are critical to the success of the policy: scope and objectives of the policy, resources, characteristics of the implementing agency, communication, external conditions, and attitudes of the implementers. The study uses a descriptive qualitative approach with data collection techniques such as in-depth interviews, observations, and documentation. Informants were purposively selected, and the data were analyzed using source triangulation and qualitative analysis techniques. Research findings indicate that the Strategi PASTI PAS has positively contributed to increasing the number of government asset certifications, the effectiveness of reporting and handling infrastructure damage, and encouraging citizen participation through Kelompok Peduli Infrastruktur (Poklitur). However, obstacles such as budget constraints, lack of coordination among policymakers, inadequate public outreach, and a lack of public technological literacy remain significant challenges. Therefore, this study highlights the importance of integrating institutional capacity and community empowerment for the implementation of adaptive and sustainable infrastructure policies.